A simple and effective approach to prepare injectable macroporous calcium phosphate cement for bone repair: Syringe-foaming using a viscous hydrophilic polymeric solution. (February 2016) - Zhang, Jingtao; Liu, Weizhen; Gauthier, Olivier; Sourice, Sophie; Pilet, Paul; Rethore, Gildas; Khairoun, Khalid; Bouler, Jean-Michel; Tancret, Franck; Weiss, Pierre
Graphical abstract: Abstract: In this study, we propose a simple and effective strategy to prepare injectable macroporous calcium phosphate cements (CPCs) by syringe-foaming via hydrophilic viscous polymeric solution, such as using silanized-hydroxypropyl methylcellulose (Si-HPMC) as a foaming agent. The Si-HPMC foamed CPCs demonstrate excellent handling properties such as injectability and cohesion. After hardening the foamed CPCs possess hierarchical macropores and their mechanical properties (Young's modulus and compressive strength) are comparable to those of cancellous bone. Moreover, a preliminary in vivo study in the distal femoral sites of rabbits was conducted to evaluate the biofunctionality of this injectable macroporous CPC. The evidence of newly formed bone in the central zone of implantation site indicates the feasibility and effectiveness of this foaming strategy that will have to be optimized by further extensive animal experiments. Statement of significance: A major challenge in the design of biomaterial-based injectable bone substitutes is the development of cohesive, macroporous and self-setting calcium phosphate cement (CPC) that enables rapid cell invasion with adequate initial mechanical properties without the use of complex processing and additives. Thus, we propose a simple and effective strategy to prepare injectable macroporous CPCs through syringe-foaming using a hydrophilic viscous polymeric solution (silanized-hydroxypropyl methylcellulose, Si-HPMC) as a foaming agent, that simultaneously meets all the aforementioned aims. Evidence from our in vivo studies shows the existence of newly formed bone within the implantation site, indicating the feasibility and effectiveness of this foaming strategy, which could be used in various CPC systems using other hydrophilic viscous polymeric solutions.